2013
DOI: 10.4236/ajps.2013.41013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a <i>Tos</i>17 Insertion Mutant of Rice Auxin Signal Transcription Factor Gene, <i>OsARF</i>24

Abstract: Auxin signaling plays a key role in the regulation of various growth and developmental processes in higher plants. Auxin response factors (ARFs) are transcription factors that regulate the expression of auxin-response genes. The osarf24-1 mutant contains a truncation of domain IV in the C-terminal dimerization domain of a rice ARF protein, OsARF24. This mutant showed auxin-deficient phenotypes and reduced sensitivity to auxin. However, OsARF24 protein contains an SPL-rich repression domain in its middle region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…d). Little information is available to distinguish between these alternatives, as the full catalogue of potential in planta ARF dimers/oligomers is not available, but the co‐expression of activator and repressor ARFs in the same tissue (Vernoux et al ) is probably functionally relevant for auxin‐dependent transcription, and in rice, the induced truncation of a repressor ARF showed that at least part of domain IV (PB1) was required for full repressor activity (Sakamoto & Inukai ).…”
Section: Auxin Response Factors Are Both Transcriptional Activators Amentioning
confidence: 99%
“…d). Little information is available to distinguish between these alternatives, as the full catalogue of potential in planta ARF dimers/oligomers is not available, but the co‐expression of activator and repressor ARFs in the same tissue (Vernoux et al ) is probably functionally relevant for auxin‐dependent transcription, and in rice, the induced truncation of a repressor ARF showed that at least part of domain IV (PB1) was required for full repressor activity (Sakamoto & Inukai ).…”
Section: Auxin Response Factors Are Both Transcriptional Activators Amentioning
confidence: 99%
“…Among the TaARF members, TaARF9 and 13 in Group IV and TaARF15 in Group VI both significantly responded to exogenous auxin. Since other ARF s in the same group, including AtARF2 , SlARF2 , OsARF1 , and OsARF24 in Group IV as well as AtARF7 , AtARF19 , OsARF19 , SlARF19 , and OsARF5 in Group VI, were confirmed to be involved in the regulatory development of plant roots, stems, and leaves ( Ellis et al, 2005 ; Inukai et al, 2005 ; Sakamoto and Inukai, 2013 ; Galvan-Ampudia and Vernoux, 2014 ; Ma et al, 2015 ; Zhang et al, 2015 ; Indoliya et al, 2016 ; Ren et al, 2017 ), it is speculated that TaARF9 , 13 , and 15 also have similar functions. In addition, the in silico expression data revealed that in Group IV, TaARF9 showed a high expression level in roots and TaARF12 as well as TaARF13 were highly expressed during seedlings, vegetative and reproductive stages in wheat.…”
Section: Discussionmentioning
confidence: 98%
“…Several genes that regulate plant architecture and organ size in relation to hormone pathways have been identified and characterized in rice. For instance, the narrow leaf mutant nal7 [17], osarf24 [68], and tryptophan-deficient dwarf mutant tdd1 [39], which are all related to the auxin pathway. The dwarf mutants gid1 [69], gid2 [70], slr1 [71], d18 [72], and sd1 [73], and the small seeds mutants oscbl5 [32] and sgsd3 [74], are related to the gibberellin pathway.…”
Section: Discussionmentioning
confidence: 99%